ANALISIS PENERAPAN AKUNTANSI PADA TOKO ZAM-ZAM DI KELURAHAN BALANDETE KECAMATAN KOLAKA - Ildayanti, Ildayanti; Turi, La Ode; Ilham, Surianto (Jurnal Akuntansi Kompetif, 2025)
Small businesses or also known as UMKM (Micro, Small and Medium Enterprises), have an important role in the economy, both in developing and developed countries. One of the contributions of UMKM is to create jobs and increase community income. Therefore it is very important for businesses to keep financial records, financial records help UMKM to determine the financial performance of the business, such as business operating costs and profit and loss. In addition, good financial records can help UMKM in having a more effective marketing strategy. The title of this research is “Analysis of Accounting Implementation at Zam-Zam Shop in Balandete Subdistrict, Kolaka District.” which is located at Jl. Pendidikan Balandete village. This reserarch aims to know how the accounting implementation carried out by the Zam-Zam Shop is in accordance with the basic concepts of accounting as for this research uses data priemer and secunder. Priemary data is coming directly from the shop owner thourgh interviws while secondary data is data obtained from other parties and not directly obtained by researchers from the subject of their research. This research method is a qualitative descriptive method. As for data collection techniques by means of observation, interviews, and documentation. Based on the results of the research that has been done, it can be concluded that the application of accounting at Toko Zam-Zam is not in accordance with applicable accounting standards